ANALYSIS OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON TEACHER PERFORMANCE WITH COMPETENCE AS AN INTERVENING VARIABLE IN HIGH SCHOOLS A SUPERIOR COUNTRY FOSTERED IN BENER MERIAH REGENCY - Roslina; Mesra B; Kiki Farida Ferine (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of leadership style and organizational culture on teacher performance with competence as an intervening variable at Unggul Binaan State Senior High School in Bener Meriah Regency. This study uses a quantitative approach with a census technique, namely the entire population of 78 teachers as the research sample. Data collection was carried out through a questionnaire whose validity and reliability were tested using the Partial Least Square (PLS) method. The results of the study indicate that organizational culture has a positive and significant effect on teacher performance, while leadership style has a positive but significant direct effect on teacher performance. However, leadership style has a positive and significant effect on teacher competence. Teacher competence is proven to have a positive and significant effect on teacher performance, and is able to mediate the influence of leadership style and organizational culture on teacher performance. The coefficient of determination value shows that the variables of leadership style and organizational culture are able to explain competence by 70.4%, while leadership style, organizational culture, and competence together explain teacher performance by 80.7%. These findings indicate the importance of strengthening organizational culture and developing teacher competence to improve teacher performance at Unggul Binaan State Senior High School in Bener Meriah Regency.